CHARACTERISTICS OF PTERYDOPHYTA IN CIWALEN RESEARCH LANE, GEDE PANGRANGO NATIONAL PARK, CISARUA, WEST JAVA - Tosca Inas Sabrina (Universitas Sultan Ageng Tirtayasa, 2018)
Pteridophtyes are a phylum of plants. They are the vascular plants (those having xylem and phloem tissues) that reproduce by releasing spores rather than seeds, and they include the highly diverse true ferns and other graceful, primarily forest-dwelling plants. There are about eleven thousand different species of pteridophytes, making them the most diverse land plants after the flowering plants (angiosperms). Pteridophytes consisting of four divisions, there are Psilophyte, Lycophyte, Sphenophyte, and Pterophyte. The purpose of this research is to know the type of division of Pteridophytes (fern), and to know the diversity of division of Pteridophyte (fern) in Ciwalen track Taman Nasional Gunung Gede Pangrango (TNGGP). The research method used is descripting and purposive sampling. The results showed identification of diversity of Pteridophytes division in Ciwalen track Taman Nasional Gunung Gede Pangrango (TNGGP) found 10 species. The spesies among others: Asplenihm nidus, Asplenium spathulinum, Asplenium tereum, Diplazium proliferum, Didymochlena truncatula, Angiopteris evecta,, Cyclosorus subpubescens, Nephrolepis sp., Nephrolepis davallioides and Selaginella opaca